Sistem Informasi Koperasi Pegawai Negeri (KPN) Universitas Mataram Berbasis Web - Desenia Mulyani Harja; Sri Endang Anjarwani; Ariyan Zubaidi (Journal of Computer Science and Informatics Engineering (J-Cosine), 2018)
The â€œKoperasi Pegawai Negeriâ€ (KPN) of Mataram University is a kind of saving/debit and loan cooperative that own by Mataram University. It is an institution cooperative which by the rule receive/collect/debit the funding (money) regularly from the members of the cooperative, as well as allows the members to get a modal credit/loan with a certain interest rate in accordance to the rule. The system to manage and carried out the saving and loan process is still under conventional system. When the members need to confirm on the data regarding their saving, loan or payment, they have to come to the office or to have to contact the admin. Accordingly, the Web based Information System is urgently needed to solve the above problems. This system was build up by mean of â€œCodeigniter Frameworkâ€ using a programmer language of PHP and HTML. The system was developed using waterfall model. Key words: Information system, saving and loan cooperative, waterfall model, codeigniter, website.